The paradoxical effects of analgesics and the development of chronic migraine - Marcelo E. Bigal (Arquivos de Neuro-Psiquiatria)
In a subgroup of individuals episodic migraine evolves into a stage where individuals have headaches on more days than not. Among the risk factors for chronification, excessive use of analgesic medications figure prominently and reviewing this topic is the scope of this article. The issue of causality is discussed and evidence suggesting that specific medications, at critical doses, are risk factors for chronic migraine (CM) is reviewed. The concept of critical dose of exposure for different classes is presented and biological plausibility and putative mechanisms are reviewed.